An item‐level investigation of conceptual and empirical distinctiveness of proactivity constructs. (31st March 2020) - Cho, Seonghee; Carpenter, Nichelle C.; Zhang, Bo
Abstract: Beyond the prior investigations that took scale‐level approaches to determining discriminant validity in proactivity constructs, the current study contributes a much‐needed interrogation of the items used to measure the behaviors in this domain. The substantive validity (SV) assessments (Study 1) showed that many of the items were judged to be inconsistent with the definition of the construct they assess or, alternatively, more consistent with the definition of a different construct in the domain. Further, exploratory factor analysis revealed the difficulty in empirically separating the four behaviors, while BiM results also advocated against the unique variance of them after accounting for a general factor (Study 2). Altogether, our results show that the items are partly to blame for the empirical redundancy issue.